Efektivitas Permainan MANGKOK (Remaja Pencegah Rokok) dalam Meningkatkan Pengetahuan dan Motivasi Siswa di SMPN 01 Lalonggasumeeto - Rosmini Rosmini; Ruslan Majid; Hartati Bahar (Pusat Riset dan Inovasi Nasional, 2023)
Cigarettes are rolls of tobacco which, when consumed, cause harmful effects to both those who smoke them and those who inhale the smoke. Many teenagers are now starting to recognize and try smoking cigarettes. The aim of this research is to find out the effectiveness of the MANGKOK (Teenager Prevent Smoking) game in increasing knowledge and motivation of teenagers at SMPN 01 Lalonggasumeeto in 2023. The research method used is a quantitative approach, Pre-Experimental design type using a one group pretest and posttest design. . The population of this study was 85 students, while the sample was 46 respondents taken using a purposive sampling technique using the Slovin formula. The results of the Paired Sample T-Test show that there is an increase in knowledge and motivation before and after being given the MANGKOK game to teenagers at SMPN 01 Lalonggasumeeto in 2023 with the respective knowledge p-value (0.000) < alpha (0.05) and p-value of motivation (0.001) < alpha (0.05). This research was carried out for 21 days.